Bricks of St. Nicholas Church: Link Between Marking and Geochemistry - Sarcevičius, Saulius; Taraškevičius, Ričardas (Archaeologia Lituana, 2016)
The bricks of St. Nicholas Church in Vilnius comprise the study object of this manuscript. The authors present the visual method of brick marks and size analysis and the geochemical method. The aims of this manuscript were the following: a) to reveal the information from marked bricks considering the issues of Church building stages and chronology, b) to present the examples of cluster analysis method application to geochemical data of brick composition demonstrating the methodical possibility to find related bricks in other buildings of Vilnius, c) to discuss the application conditions which could give more successful results of brick geochemical comparison on the basis of which both technological and chronological issues of brick production could be solved. The studies of old brick walls have a long tradition in Lithuania. The pioneer of such studies was Marijanas Moreliovskis who formulated the main research areas and issues for future generations during pre-war period. The scholar noted the changes of brick size and tie up methods during ages. The proportional-chronological regularities of the old bricks were used by many later scholars as well, almost exclusively by the architects. Using this method, the architects have determined the chronological boundaries of St. Nicholas Church: from the second half of the 14th century to the 15th century. Meanwhile, the positions of other researchers on this issue are very different. Some historians attribute the building of Church to the Grand Dukes’ Vytenis and Gediminas period, i.e., the junction of the 13th and 14th centuries. They were especially pleased by the date obtained during archaeomagnetic studies of bricks: 1297–1310. However, according to the major part of historians, the foundation of brick Church took place in the period between 1382 and 1413, they relate it to Hanul, vice-regent of Vilnius, merchant of Riga and follower of Jogaila. Solving St. Nicholas Church dating issue, the authors paid attention to the methodical problems of fixing the specificity of the former brickyard production. Both visual and geochemical methods were applied by the authors in search of the similarities or differences of brick production technology. Using the visual method, the attention was paid to the Church wall bricks with marks on their sides (these marks were pressed into bricks before their burning). Total number of marked bricks found was 11. They were marked using round dies with different ornamentation that can be divided into four types. Most of them were found in the southern facade of the Church (Fig. 1). Comparing the marked brick line-up and the changes of brick size in the southern and in the western façade (Figs. 2–4), the authors draw two conclusions. The first one is that the southern and the western walls of the church were built at the same primary time. At least two different marks (Fig. 1, types 1 and 2) were used during this building stage. Basing on analogous marked bricks from St. Ann-Barbara Church with two different signs pressed into the same brick, the authors are inclined to suppose that the bricks of St. Nicholas church marked by stamps of types 1 and 2 were also produced in the same brickyard. The second conclusion is that the frontage of western façade of the Church was built or rebuilt later (probably in the 16th century). The marked bricks of type 3 are found there (Fig. 1). Basing on analogous marked bricks from Vilnius, the authors express their opinion that the brickyard, which produced these bricks, could supply its production also to other buildings of that time: Cathedral and St. Virgin Mary (Franciscan) Church (Figs. 6, 7). The authors express their opinion that the tradition of marking the bricks came to Vilnius from the west. According to analogous marked bricks from the towns of the north-eastern Germany (Fig. 5) it is concluded that St. Nicholas Church could be built not earlier than in the 7th decade of the 14th century. So, the position of Hanul times Church becomes more reasonable. The second method selected by the authors for determination of technological properties of bricks is geochemical. One of the multivariate statistical methods, i.e., the hierarchical cluster analysis is applied to the quantitative data of chemical element contents in bricks. The groups of samples are distinguished during this analysis according to similarity of chemical element contents. This method was used aiming to find out whether the bricks of St. Nicholas Church are similar in chemical composition and whether they are similar or different in comparison with bricks from other Vilnius buildings of the 14th–16th centuries. Five bricks from St. Nicholas Church were compared with 52 bricks of other buildings in Vilnius, dated back from 1326 to 1526. They are as follow: Franciscan Church of the St. Virgin Mary, early Cathedral and the Lower Castle (Table). The result of cluster analysis is that three bricks of St. Nicholas Church early stage have very similar chemical composition. This composition is most of all similar to the brick samples taken from the Franciscans Church and from the northern gate tower of Lower Castle (Figs. 8–10). However, the authors emphasise that the conclusions based on geochemical results are more or less only preliminary and informing about methodological possibilities. In future, aiming to obtain more precise interpretation of brick origin and technological processes according to geochemical research data, it would be useful to ensure the following conditions: a) to take more than one sub-sample from the same brick (avoiding the effect of accidental sample selection), b) to take samples from the inner part of the brick (avoiding anthropogenic geochemical load), c) to use multivariate analysis method (not less than 20 chemical elements) with determination of total content of each chemical element (Taraškevičius et al., 2013, p. 15), d) to compile geochemical database of exactly dated bricks (when a, b and c conditions are fulfilled), e) to select the set of chemical elements for multivariate analysis basing on various geochemical features (not only variability of sample composition); f) to verify and adjust the results of cluster analysis with the help of other multivariate statistical methods; g) to accumulate geochemical data on the deposits of potential raw material (clay). The fulfilment of the last condition can be most of all complicated. Hence, the search for these deposits and their specialised archaeological and geochemical investigations become the crucial objects of future research. Without such data, there exists the sore point of selection of chemical elements for cluster analysis. Taking into account that until now there is a large set of unknown variables, the possibility to reveal useful regularities in presented illustrations with cluster diagrams stimulates the hope that both the described and the other potential complexes of geochemical methods can be successfully used to obtain the knowledge about technological processes of the past.